Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Informasi Laporan Keuangan Pemerintah Daerah - Muflihah muflihah (Jambura Accounting Review, 2021)
The purpose of this study was to determine and test Human Resources, Information Technology, Internal Control Systems, Information Value, Financial Control to influence financial statements. This type of research is using quantitative methods using linear regression test. The population in this study were all SKPDs in Pamekasan Regency with the number of SKPD 45 which was carried out by selecting subjects using purposive sampling method. Based on the analysis of research data, it is known through a partial test that Human Resources have a significant effect on the Quality of Regional Financial Reports, Information Technology has no effect on the Quality of Regional Financial Reports, the Internal Control System has a significant effect on the Quality of Regional Financial Reports, Information Value has no significant effect on Quality of Regional Financial Reports, Financial Control has a significant effect on the Quality Financial Statements in Pamekasan Regency.